2021
DOI: 10.1177/15347354211062639
|View full text |Cite
|
Sign up to set email alerts
|

Echinacoside Suppresses the Progression of Breast Cancer by Downregulating the Expression of miR-4306 and miR-4508

Abstract: The main treatment of breast cancer includes surgical resection, radiotherapy, chemotherapy, endocrine therapy, and molecular targeted therapy, but the outcomes remain unsatisfactory. Previous studies demonstrated that echinacoside, microRNA (miRNA/miR)-4306 and miR-4508 were associated with lymph node metastasis, chemoresistance and self-renewal capability in breast cancer, but in-depth studies on the underlying mechanism of their anticancer effects have not been performed to date. In order to identify the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Various molecular biological studies on the anti-cancer activity of echinacoside have been demonstrated both in vitro and in vivo in some studies. In these studies, echinacoside has been reported to reduce cell proliferation, cell invasion and migration-inhibited colony formation of various cancer cell lines [14,15,[20][21][22]27]. It was recently reported that echinacoside inhibits breast cancer cell growth under in vitro conditions via Wnt/ β-catenin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various molecular biological studies on the anti-cancer activity of echinacoside have been demonstrated both in vitro and in vivo in some studies. In these studies, echinacoside has been reported to reduce cell proliferation, cell invasion and migration-inhibited colony formation of various cancer cell lines [14,15,[20][21][22]27]. It was recently reported that echinacoside inhibits breast cancer cell growth under in vitro conditions via Wnt/ β-catenin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroprotective, hepatoprotective, immune modulator, antidiabetic and anticancer activities of echinacoside have been demonstrated in previous studies [15][16][17][18][19]. It has been reported that echinacoside exhibits anticancer activity through cellular mechanisms such as triggering apoptosis, cell cycle arrest, and inhibition of cell proliferation in various cancers such as breast [14] colon [15], pancreas [20], ovary [21] and liver [22]. There is no comprehensive molecular mechanistic study on echinacoside and prostate cancer in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Echinacoside (ECH), a natural phenylethanoid glycoside, is the main active ingredient presenting in Cistanche salsa, which has been reported to be extensively studied in neuroprotection (Lu et al, 2016), antitumor (Ye et al, 2019), anti-aging (Wu et al, 2019), and myocardial remodeling (Ni et al, 2021), antioxidant (Chuang et al, 2022), anti-apoptotic (Zhang et al, 2017), and anti-inflammatory (Zhou et al, 2020). Studies have demonstrated that ECH alleviates hypoxia-induced memory impairment (Zheng et al, 2019), inhibits the development of breast cancer (Bian et al, 2021), alleviates inflammatory bowel disease (Li et al, 2018), and improves heart failure by reversing myocardial remodeling (Ni et al, 2021). ECH has also been found to promote bone formation by enhancing osteoblast proliferation and differentiation as well as alleviating the reduction in bone mass caused by diabetes (Gong et al, 2019) or ovariectomy (Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Echinacoside (ECH) is a primary natural bioactive ingredient derived from Cistanches Herba and Echinacea that has a variety of biological effects, such as neuroprotection, 13 myocardial protection, 14 liver protection, 15 immune regulation, 16 anti-tumor 17–20 and other pharmacological effects. In recent years, a line of studies has indicated that ECH has an anticancer effect on various tumors.…”
Section: Introductionmentioning
confidence: 99%